The Arab Spring Will It Lead to Democratic Transitions? - Henry, Clement; Ji-Hyang, Jang.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
This timely project on the Arab Spring was initiated to provide The Asan Institute's own assessment of the changes currently taking place in the region and their significant implications for South Korea.
Keywords: Science; Science; Science, general